IMAGING OF PRIMARY CARDIAC TUMORS IN CHILDREN: A SYSTEMATIC REVIEW - Emeraldo Sierang (PT Wahana Global Education, 2025)
Primary cardiac tumors in children are rare, and imaging is central to their diagnosis and management. While echocardiography, cardiac MRI, CT, and PET are used in clinical practice, the comparative evidence base remains fragmented. To systematically review the role of imaging modalities in the detection and characterization of primary cardiac tumors in the pediatric population. A systematic search of PubMed was performed. Eligible studies included children (<18 years) with primary cardiac tumors and reported imaging findings. Study designs considered were case reports, case series, diagnostic cohorts, and narrative reviews. Data were extracted on study type, tumor type, imaging modality, and diagnostic outcomes. Thirty studies were included. Echocardiography was consistently reported as the first-line modality due to availability and safety. Cardiac MRI provided detailed tissue characterization and showed good accuracy in differentiating tumor types, particularly rhabdomyomas and fibromas. CT contributed to the assessment of calcification, vascular involvement, and extracardiac extension. PET was rarely reported, but may have value in assessing malignant lesions. Evidence quality was limited by small sample sizes and heterogeneity, precluding meta-analysis. Imaging is essential for the diagnosis and management of primary pediatric cardiac tumors. A multimodal approach enhances diagnostic accuracy, with modality selection tailored to clinical context and resource availability. Future multicenter studies are needed to validate standardized imaging protocols.